Quantitative investigation of micro slip and localization in polycrystalline materials under uniaxial tension - Zhang, Z; Lunt, D; Abdolvand, H; Wilkinson, A; Preuss, M; Dunne, F (Elsevier, 2018)
Micro slip activation and localization in Ti-6Al-4V deformed in tension have been examined quantitatively using high-resolution (HR) digital image correlation (DIC), HR-electron backscatter diffraction (EBSD) and crystal plasticity finite element modelling. The measured polycrystal slip, strain, lattice rotation and geometrically necessary dislocation (GND) density distributions are generally well captured by the a priori crystal plasticity model based on the rate-sensitive properties of α-titanium. An overall slip trace analysis showed over 80% agreement between HR-DIC and crystal plasticity modelling of the primary slip activation. The texture beneath the characterised free-surface has been found to affect the local slip, stress distribution, lattice curvature and GND density and three texture variations have been considered. Grain-level slip trace analysis shows that the crystal plasticity modelling can capture single (straight) slip, multiple slip activation and complex wavy slip. The latter has been found to result from the interaction of independently activated basal and prismatic slip systems with common slip direction. Initial inter-granular misorientations greater than about 5° have been shown to influence the subsequent micromechanical grain behaviour including slip, lattice rotation and GND density. This work contributes to the understanding of slip localization and load shedding in dwell fatigue in polycrystalline hexagonal materials.